The Influence of Perceived Ease of Use, Social Influence, Trust, Technology Self-Efficacy and Security on Intention to Use One of Digital Bank in D.I. Yogyakarta - Silvika Rina Fatin Serzya (International Journal of Social, Economic, and Business, 2025)
This study aims to analyze factors influencing the intention to adopt one of the digital banks in D.I. Yogyakarta region, focusing on perceived ease of use, social influence, trust, technology self-efficacy, and security. Data was collected through questionnaires distributed to respondents who are Generation Z and users of a well-known conventional bank in Indonesia, but who have not yet used the digital bank services offered by the bank’s subsidiary. The data was analyzed using SPSS 25 and TAM and TAM 2 methods as theoretical basis. The results show that perceived ease of use, social influence, and security have a significant positive influence on user intention. Ease of use enhances user convenience, social influence—particularly from peers and family—encourages adoption, and security is a critical factor as users prioritize the safety of financial transactions. These findings offer practical insights for improving digital bank adoption strategies within similar demographic segments.